Towards understanding the electronic structure and ion fragmentation patterns of indole and related compounds. Issue 10 (January 2020) - Sa'adeh, H; Plekan, O; Ponzi, A; Toffoli, D; Bolognesi, P; Chiarinelli, J; Castrovilli, M C; Vozzi, C; Faccialà, D; Devetta, M; Ciavardini, A; Avaldi, L; et al.
Synopsis: Electronic structure and VUV-induced fragmentation of selected molecules of the indole family have been studied using valence photoemission spectroscopy (PES), core X-ray photoelectron spectroscopy (XPS), near-edge X-ray absorption fine structure (NEXAFS) and Photo-Electron Photo-Ion Coincidence (PEPICO).